The Dynamic of the United States Political Elites Construction on Taliban in Afghanistan (Case Study of the US Presidents’ Throughts on Terrorism Policies, from President Josh W. Bush to President Joe Biden in 2001-2021) - Muhammad Arif Ikhsanudin (Formosa Journal of Social Sciences (FJSS), 2023)
This study aims to find out and analyze how the thought construction of the president of the United States can influence policies on eradicating terrorism and the war between the US and the Taliban that has been going on for 20 years. The US government began to focus more on terrorism after September 11, 2001, or the so-called 9/11 tragedy, which caused the two symbols of the United States, the World Trade Center (WTC) and the Pentagon, to become targets for attacks by Al-Qaeda. The leader of Al-Qaeda, Osama bin Laden, is known to be hiding in Afghanistan, the territory of the Taliban. The US considered the Taliban to be protecting Osama, so it immediately sent military troops to Afghanistan, and war broke out between the US and the Taliban. During these two decades, the United States has been led by four presidents with different constructions of thought in providing policies, particularly on the issues of terrorism and the war in Afghanistan. Based on this, the authors analyze the thought construction of each president to see the impact of the US Presidential Policy in fighting terrorism and the war between US and Taliban in Afghanistan